Whole Plant Temperature Manipulation Affects Flavonoid Metabolism and the Transcriptome of Grapevine Berries - Pastore, Chiara; Dal Santo, Silvia; Zenoni, Sara; Movahed, Nushin; Allegro, Gianluca; Valentini, Gabriele; Filippetti, Ilaria; Tornielli, Giovanni Battista (Frontiers in Plant Science, 2017)
Among environmental factors, temperature is the one that poses serious threats to viticulture in the present and future scenarios of global climate change. In this work, we evaluated the effects on berry ripening of two thermal regimes, imposed from veraison to harvest. Potted vines were grown in two air-conditioned greenhouses with High Temperature (HT) and Low Temperature (LT) regimes characterized by 26 °C and 21 °C as average and 41.7 °C and 35 °C as maximum air daily temperature, respectively. We conducted analyses of the main berry compositional parameters, berry skin flavonoids and berry skin transcriptome on HT and LT berries sampled during ripening. The two thermal conditions strongly differentiated the berries. HT regime increased sugar accumulation at the beginning of ripening, but not at harvest, when HT treatment contributed to a slight total acidity reduction and pH increase. Conversely, growing temperatures greatly impacted on anthocyanin and flavonol concentrations, which resulted as strongly reduced, while no effects were found on skin tannins accumulation. Berry transcriptome was analyzed with several approaches in order to identify genes with different expression profile in berries ripened under HT or LT conditions. The analysis of whole transcriptome showed that the main differences emerging from this approach appeared to be more due to a shift in the ripening process, rather than to a strong rearrangement at transcriptional level, revealing that the LT temperature regime could delay berry ripening, at least in the early stages. Moreover, the results of the in-depth screening of genes differentially expressed in HT and LT did not highlight differences in the expression of transcripts involved in the biosynthesis of flavonoids (with the exception of PAL and STS) despite the enzymatic activities of PALs and UFGT being significantly higher in LT than HT. This suggests only a partial correlation between molecular and biochemical data in our conditions and the putative existence of post-transcriptional and post-translational mechanisms playing significant roles in the regulation of flavonoid metabolic pathways and in particular of anthocyanins.